PENGARUH TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 14 PADANG - Zulfikarni, Rafika, Harris Effendi Thahar, (Universitas Negeri Padang, 2017)
This article was written to detect the influence of modelling concerning short story writing skill of class IX students of SMPN 14 Padang. The data of this research were the result of the short story writing final test. The data were collected by giving short story writing test through modelling and without modelling. The hipotesis tested by using test-t formula. The result indicated that (1) the arithmetic average of the students’ short story writing skills pretest 58,85; (2) the arithmetic average of the students’ short story writing skills posttest were 86,97; and (3) according to test-t’s result, can be concluded that there was a significant influence of the used of modelling to the short story writing skill of class IX students of SMPN 19 Padang. Kata kunci: pengaruh, teknik pemodelan, menulis cerpen